Iron interference in hemoglobin production in piglets from birth to weaning - Cruz, Nathan R.N. [UNESP]; Baraldi, Thaís G. [UNESP]; Marinho Neto, Fausto A. [UNESP]; Alvarenga, Patrícia V.A. [UNESP]; Oliveira, Juliana P. [UNESP]; Albuquerque, Ana C.A. [UNESP]; Brito, Helena C.D. [UNESP]; Nascimento, Larissa A.B. [UNESP]; Oliveira, Luís G. [UNESP]; Santana, Aureo E. [UNESP] (FapUNIFESP (SciELO), 2023)
Iron deficiency anemia (IDA) in humans is defined as the decrease of total hemoglobin concentration and the non-production of the adult hemoglobin subtype 2 - HbA2 (α2δ2 chains), which is considered a marker of IDA severity in humans, dosed together with the iron serum. This study aimed to determine the standard of hemoglobin types in piglets induced to experimentally IDA in the first 21 days of life (delivery to weaning). In the present study, 40 piglets born from four naïve gilts, were randomly and equally assigned among the gilts. On the third day after delivery, the groups were randomly distributed in different environments (cement and clay floors) and according to the iron supplementation (iron dextran and placebo). Erythrocyte parameters, serum iron, and hemoglobin trait were analyzed at four moments between birth and weaning days. The group of piglets that did not receive iron dextran supplementation on the third-day post-birth and were placed in the pen without soil did not present HbA2 from the seventh day onwards on the agarose electrophoretogram (pH 8.6) and this observation was correlated to decrease of serum iron (ρ: 0.156, p=0.003) when compared to the other groups' piglets that did not present iron deficiency. In the present study was possible to determine the swine hemoglobin pattern in IDA, since HbA2 was absent in piglets with IDA in comparison to the non-ferropenic groups and the correlation between the reduction of iron levels and the absence of HbA2.
Keywords: electrophoresis; HbA2; hemoglobinopathy; iron deficiency anemia; piglets; pigs; Swine